THE IMPLICATIONS IN THE USE OF ENGLISH AS THE MEDIUM OF INSTRUCTION IN BUSINESS MANAGEMENT COURSES AT VAVUNIYA CAMPUS - Gnanaseelan, J.; Jeyaseelan, S. (University of Jaffna, 2019)
The paper avails, in a systemic form, some of the results of the investigation into nature, functions, problems, and implications in the use of English as the Medium of Instruction (EMI) in the Business Management courses at Vavuniya Campus of the University of Jaffna, located in the conflict-affected northern part of Sri Lanka. It is a case study of the responses of the students and the teachers from Tamil and Sinhala language communities of the Faculty of Business Studies. This paper analyzes the perceptions on the use of the medium, the EMI background, resources available and accessible, language abilities of the teachers and learners, learning style and pedagogy, the EMI methodology, the socio-economic and socio-political contexts typical of a non-native English learning context. The analysis is quantitative and qualitative. It finds out the functional perspective of the EMI in Sri Lanka and suggests practical strategies of contextualization and acculturation in the EMI organization and positions. The paper assesses the learner and teacher capacity in the use of English. The ethnic conflict and linguistic politics in Sri Lanka have contributed multiple factors to the current use of English as the medium. It has conflicted with its domestic realities and the globalization trends of the world at large, which determines efficiency and effectiveness.
Keywords: English medium; function; learning; management; teaching